CYBERDESPAIR: A Screenplay Raising Awareness of Social Media Addiction - Shannen Tanusudiro (Institute of Research and Community Outreach - Petra Christian University, 2023)
This thesis is created with the purpose to raise awareness in social media addiction and how it affects the people we are close with. Social media is commonly used by everyone in this modern era, but not a lot of users are aware of the danger and risk it can bring to us and social media addiction is an unhealthy reliance on online platforms. By using Erik Erikson’s psychological development theory, this thesis will explore the reasons, causes and effects on why an individual is addicted to social media. It will emphasize using the fourth, fifth, sixth as well as the final stage of Erikson’s psychological development stages to support the story building. Using modern tragedy as its genre, this thesis will show the story of Nathan and Sydney's social media addiction and how eventually the two characters end up crossing paths in the real world.